Synthesis method of silicon dioxide crystal with high birefringence
By applying high temperature and high pressure conditions to synthesize quartz in a large cavity press, the problem of low birefringence of silica quartz is solved, and the synthesis of high birefringence silicon dioxide crystals is achieved, with better performance than traditional materials and environmentally friendly.
Patent Information
- Application Number
- CN202411075430.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-07
- Publication Date
- 2025-03-21
AI Technical Summary
Silica quartz has a low birefringence index and is difficult to meet the needs of high-performance optical devices.
By applying high temperature and high pressure conditions of 20-25 GPa and 1500-2000 degrees Celsius in a large cavity press, high birefringence silica crystal quartz was synthesized for at least 12 hours to promote crystal growth.
It significantly improves the birefringence of silica, reaching 5 times the birefringence of quartz, and has better performance than commercial magnesium difluoride. The synthesis process does not require doping heavy metals or organic solvents, and is environmentally friendly.
Smart Images

Figure CN119663443A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of optical equipment material synthesis, and in particular relates to a method for synthesizing high-birefringence silicon dioxide crystals. Background Art
[0002] Birefringent crystals have two refractive indices and can split light into two linearly polarized lights. This optical anisotropy makes birefringent crystals a key material for designing optical devices such as polarizers, optical isolators, wave plates, and phase compensators. Therefore, there is an urgent need to develop birefringent crystals with reasonable cost and stable structure.
[0003] To improve the birefringence of crystals, the strategies currently used mainly include chemical doping of birefringent active modules and construction of low-dimensional structures. For example, by introducing strong polar anisotropic functional modules, the optical anisotropy in single crystals can be greatly enhanced, thereby improving the birefringence. Crystals with low-dimensional frameworks also generally have higher birefringence than bulk structures. These strategies can reduce the symmetry of crystals and improve the birefringence performance of crystals.
[0004] In recent years, in the field of material design, more and more researchers have adopted high temperature and high pressure technology to synthesize new materials and obtain material properties that cannot be obtained at room temperature and pressure. The molecular formula of silicon dioxide is It is widely distributed on the surface of the earth and is one of the most abundant minerals in nature. The stable structure of silicon dioxide at room temperature and pressure is called quartz. Although quartz has only a weak birefringence (Δn≈0.009) in the visible light band of 430-860 nanometers, it is a commonly used birefringent crystal because of its high reserves. It is necessary and of great technical importance to synthesize a new structure of silicon dioxide with a higher birefringence. Summary of the invention
[0005] The purpose of the present invention is to provide a method for synthesizing high birefringence silicon dioxide crystals to solve the problem of low birefringence of silicon dioxide quartz.
[0006] The objective of the present invention is achieved through the following technical solutions:
[0007] A method for synthesizing high birefringence silicon dioxide crystals comprises the following steps:
[0008] A. Sample assembly: The initial sample of the mixture of silica and water is placed in the assembly, and the sample is assembled using a large cavity press;
[0009] B. Sample loading: First, place the LaCrO3 furnace in the center of the MgO octahedron for sample heating. After the sample powder is loaded and compacted, it is welded and sealed. Insert a D-type thermocouple from the middle of the edge of the MgO octahedron, and its hot junction is set at the center of the capsule surface.
[0010] C. After the sample is loaded, the assembly is placed in a Kawai type large cavity press for the synthesis of high water content quartz, and a high temperature and high pressure of 20-25GPa and 1500-2000 degrees Celsius are applied during the synthesis process;
[0011] D. Test after taking out: Turn off the power of the heater to quickly reduce the temperature to room temperature, slowly decompress the sample to normal pressure and then take it out for testing.
[0012] Furthermore, in step A, the mixed initial sample of silicon dioxide and water is a starting material sample of amorphous silicate SiO2·0.6H2O.
[0013] Further, in step A, a tungsten carbide anvil with a matching truncated side length of 8 mm on the long side and 3 mm on the short side is assembled, and the assembly frame is a chromium-doped magnesium oxide regular octahedron with a side length of 3 mm.
[0014] Furthermore, in step B, the center of the heating furnace is a sample capsule with a platinum shell. The platinum shell is used to prevent moisture in the sample from escaping. The platinum capsule is electrically insulated from the heater using a magnesium oxide sleeve and two covers.
[0015] Further, in step B, the hot junction of the D-type thermocouple is arranged at the center of the capsule surface.
[0016] Further, in step C, during synthesis, the assembly is first compressed to a target pressure of 23 GPa and hydraulically pressurized for 8 hours; then the temperature of the power supply is increased to a target temperature of 1600 degrees Celsius at a rate of 100 degrees Celsius per minute; after reaching the target conditions of 23 GPa and 1600 degrees Celsius, the temperature fluctuation must be maintained at no more than ±10 degrees Celsius for at least 12 hours to promote crystal growth.
[0017] Compared with the prior art, the present invention has the following beneficial effects:
[0018] 1. The present invention uses silicon dioxide commonly used in the industry as a raw material, uses high temperature and high pressure as a synthesis method, and does not require the addition of heavy metals, organic solvents and other potential pollutants during the synthesis process, which is environmentally friendly; the synthesized quartz has a birefringence of 5 times that of quartz, and its performance is better than the birefringence of commercial magnesium difluoride;
[0019] 2. This method can greatly improve the birefringence of silica quartz. While the resulting new silica structure has excellent optical properties, this method also has the advantages of sufficient raw materials and pollution-free synthesis. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0021] Figure 1 is a schematic diagram of the synthetic sample assembly;
[0022] Figure 2 This is the Raman spectrum of silica quartz;
[0023] Figure 3 It is the original interference color of silica quartz under orthogonal polarized light;
[0024] Figure 4 It is the silicon dioxide quartz in a state of complete extinction;
[0025] Figure 5 This is a graph of the thickness of silica quartz;
[0026] Figure 6 is the crystal orientation of silica quartz determined by single crystal XRD. DETAILED DESCRIPTION
[0027] The present invention will be further described below in conjunction with embodiments:
[0028] The present invention will be further described in detail below in conjunction with the accompanying drawings and embodiments. It is to be understood that the specific embodiments described herein are only used to explain the present invention, rather than to limit the present invention. It should also be noted that, for ease of description, only parts related to the present invention, rather than all structures, are shown in the accompanying drawings.
[0029] It should be noted that similar reference numerals and letters represent similar items in the following drawings, so once an item is defined in one drawing, it does not need to be further defined and explained in the subsequent drawings. At the same time, in the description of the present invention, the terms "first", "second", etc. are only used to distinguish the description and cannot be understood as indicating or implying relative importance.
[0030] In view of the low birefringence of quartz, the object of the present invention is to significantly improve the birefringence performance of silicon dioxide crystals. Specifically, by applying 20-25GPa and 1500-2000 degrees Celsius of high temperature and high pressure conditions, the crystal structure of quartz is changed from P3121 to P42 / mnm, becoming stable quartz under high pressure. At the same time, 15.3 mass percent of water is added and kept at high temperature and high pressure for at least 12 hours to promote the growth of quartz crystals. In the process of returning to normal pressure, quartz will not restore the quartz structure due to the withdrawal of pressure, therefore, the optical properties of the high pressure structure can be preserved. Using a polarizing microscope to measure the birefringence of quartz under normal pressure, it is found that its birefringence is increased by about 4 times, reaching Δn≈0.044.
[0031] The method for synthesizing high birefringence silicon dioxide crystals of the present invention comprises the following steps:
[0032] 1. Sample assembly: The starting material sample of amorphous silica (SiO2·0.6H2O) was placed in the assembly. The sample was assembled using a large cavity press. The assembly matched the tungsten carbide anvil with a long side of 8 mm and a short side of 3 mm. The assembly frame was a chromium-doped magnesium oxide regular octahedron with a side length of 3 mm.
[0033] 2. Sample loading: When loading samples, first place the LaCrO3 furnace in the center of the magnesium oxide octahedron for sample heating. The center of the heating furnace is a sample capsule with a platinum shell. The platinum shell is used to prevent moisture from escaping from the sample. After the sample powder is loaded and compacted, it is welded and sealed. The platinum capsule is electrically insulated from the heater using a magnesium oxide sleeve and two covers. A D-type thermocouple is inserted from the middle of the edge of the magnesium oxide octahedron, and its hot junction is set at the center of the capsule surface.
[0034] 3. After the sample is loaded, the assembly is placed in a Kawai type large cavity press for the synthesis of high water content quartz, applying 200,000-250,000 atmospheres (GPa) and 1500-2000 degrees Celsius of high temperature and high pressure.
[0035] During synthesis, first, the assembly is compressed to a target pressure of 23 GPa. The pressurization is hydraulic, so the pressure increase process is nonlinear. Generally speaking, the pressure rises faster in the early stage and then gradually stabilizes. The whole process takes about 8 hours. Then, the temperature of the power supply is increased to a target temperature of 1600 degrees Celsius at a rate of 100 degrees Celsius per minute. After reaching the target conditions of 23 GPa and 1600 degrees Celsius, the temperature fluctuation must be kept within ±10 degrees Celsius for at least 12 hours to promote crystal growth. Subsequently, the power of the heater is turned off to allow the temperature to drop rapidly to room temperature, and the sample is slowly decompressed to normal pressure and taken out for testing.
[0036] The present invention completes the synthesis after maintaining the high temperature and high pressure conditions of 23GPa and 1900 degrees Celsius for 12 hours. Although the quartz sample can be synthesized at the boundary pressure, such as 20 or 25GPa, the grain size is small, which is not conducive to optical testing.
[0037] 4. Return the sample after high temperature and high pressure treatment to normal pressure, take it out and test it.
[0038] The present invention uses high temperature and high pressure technology to synthesize a high-pressure structure of silicon dioxide, which has a high birefringence and remains structurally stable after returning to normal pressure. SiO2 under normal pressure not only has a high birefringence, but also has sufficient reserves of raw materials in nature, which can meet the design requirements of specific optoelectronic devices.
[0039] Example 1
[0040] A method for synthesizing high birefringence silicon dioxide crystals comprises the following steps:
[0041] 1. Sample assembly.
[0042] In this embodiment, amorphous silica (SiO2·0.6H2O) is used as the starting material. The chemical reaction of amorphous silicon dioxide is more complete than that of crystalline materials, which is conducive to the growth of crystalline materials. In addition, the starting material contains 15.3% by mass of water. Figure 1 The large cavity press assembly shown ( Figure 1 ), assemble a tungsten carbide anvil with a matching truncated side length of 8 mm on the long side and 3 mm on the short side, which is used to transmit and amplify pressure. The assembly frame is a chromium-doped magnesium oxide regular octahedron with a side length of 3 mm, which plays the role of transmitting pressure and insulation.
[0043] 2. Sample loading. When loading the sample, first place the LaCrO3 furnace in the center of the magnesium oxide octahedron, which is used for sample heating. The center of the heating furnace is a sample capsule with a platinum shell. The platinum shell is used to prevent the moisture in the sample from escaping and play a sealing role. After the sample powder is loaded and compacted, it is welded and sealed. The platinum capsule is electrically insulated from the heater using a magnesium oxide sleeve and two covers. In order to monitor the sample temperature, a D-type thermocouple is inserted from the middle of the edge of the magnesium oxide octahedron, and its hot junction is set at the center of the capsule surface.
[0044] 3. Synthesis of high water content quartz. After loading, the assembly is placed in a Kawai type large cavity press for synthesis.
[0045] During synthesis, first, the assembly is compressed to a target pressure of 23 GPa. The pressurization is hydraulic, so the pressure increase process is nonlinear. Generally speaking, the pressure rises faster in the early stage and then gradually stabilizes. The whole process takes about 8 hours. Then, the temperature of the power supply is increased to a target temperature of 1600 degrees Celsius at a rate of 100 degrees Celsius per minute. After reaching the target conditions of 23 GPa and 1600 degrees Celsius, the temperature fluctuation must be kept within ±10 degrees Celsius for 12 hours to promote crystal growth. Subsequently, the power of the heater is turned off to allow the temperature to drop rapidly to room temperature, and the sample is slowly decompressed to normal pressure and taken out for testing.
[0046] Raman spectroscopy was used to measure the crystal form of the synthesized samples, such as Figure 2 The standard peaks marked in the figure are basically consistent with those of quartz, proving that the high-pressure structure can be preserved to normal pressure.
[0047] When testing the birefringence of a crystal, a polarizing microscope is required. Under orthogonal polarized light, quartz exhibits a secondary pink interference color, such as Figure 3 shown.
[0048] These synthetic quartz crystal samples can achieve complete extinction, such as Figure 4 As shown, it was confirmed that it was a high-purity single crystal with no internal stress.
[0049] like Figure 5 The thickness of the crystal can be measured by stereomicroscopy and oriented by X-ray diffraction, as shown in Figure 6 The birefringence value of quartz at 550nm was finally measured under a polarizing microscope and was Δn=0.044.
[0050] Note that the above are only preferred embodiments of the present invention and the technical principles used. Those skilled in the art will understand that the present invention is not limited to the specific embodiments described herein, and that various obvious changes, readjustments and substitutions can be made by those skilled in the art without departing from the scope of protection of the present invention. Therefore, although the present invention has been described in more detail through the above embodiments, the present invention is not limited to the above embodiments, and may include more other equivalent embodiments without departing from the concept of the present invention, and the scope of the present invention is determined by the scope of the appended claims.
Claims
1. A method for synthesizing high birefringence silicon dioxide crystals, characterized in that: The following steps are involved: A. Sample assembly: The initial sample of the mixture of silica and water is placed in the assembly, and the sample is assembled using a large cavity press; B. Sample loading: First, place the LaCrO3 furnace in the center of the MgO octahedron for sample heating. After the sample powder is loaded and compacted, it is welded and sealed. Insert a D-type thermocouple from the middle of the edge of the MgO octahedron, and its hot junction is set at the center of the capsule surface. C. After the sample is loaded, the assembly is placed in a Kawai type large cavity press for the synthesis of high water content quartz, and a high temperature and high pressure of 20-25GPa and 1500-2000 degrees Celsius are applied during the synthesis process; D. Test after taking out: Turn off the power of the heater to quickly reduce the temperature to room temperature, slowly decompress the sample to normal pressure and then take it out for testing.
2. A method for synthesizing a high birefringence silicon dioxide crystal according to claim 1, characterized in that: In step A, the mixed initial sample of silicon dioxide and water is a starting material sample of amorphous silica SiO2·0.6H2O.
3. A method for synthesizing a high birefringence silicon dioxide crystal according to claim 1, characterized in that: Step A, assembling a tungsten carbide anvil with a matching truncated side length of 8 mm on the long side and 3 mm on the short side, and assembling a frame into a chromium-doped magnesium oxide regular octahedron with a side length of 3 mm.
4. A method for synthesizing a high birefringence silicon dioxide crystal according to claim 1, characterized in that: Step B, the center of the heating furnace is a sample capsule with a platinum shell. The platinum shell is used to prevent moisture in the sample from escaping. The platinum capsule is electrically insulated from the heater using a magnesium oxide sleeve and two covers.
5. The method for synthesizing a high birefringence silicon dioxide crystal according to claim 1, characterized in that: In step B, the hot junction of the D-type thermocouple is set at the center of the capsule surface.
6. A method for synthesizing a high birefringence silicon dioxide crystal according to claim 1, characterized in that: Step C, during synthesis, first compress the assembly to a target pressure of 23 GPa and apply pressure using oil hydraulic pressure for 8 hours; then increase the temperature of the power supply at a rate of 100 degrees Celsius per minute to a target temperature of 1600 degrees Celsius; after reaching the target conditions of 23 GPa, 1600 degrees Celsius, the temperature fluctuation must be maintained at no more than ±10 degrees Celsius for at least 12 hours to promote crystal growth.